ESSENCE, CONTENT AND ROLE OF STATE AUDIT IN THE SYSTEM OF STATE FINANCIAL CONTROL - G.A. Rakhimova,; G.Zh. Esenova,; B.T. Nazhmidenov,; A.A. Kabiev, (Academic Journal of Physical and Chemical Sciences, 2021)
State financial control as a complex category is, in the opinion of most scholars, an integral part of the concept of “governance”, which, in turn, derives from the essence of power and the state. Like any element of these categories, control has its place in public administration. The control allows to ensure the competence and concreteness of the management, i.e., management based on reliable information, having which you can timely notice the errors and obstacles to the goal, overcome them, adjusting the management, bringing it in line with objective changes, develop the most appropriate solutions to various general and special issues of public life. If we talk about financial control, it should be noted that financial control can be viewed as a function of management activities, but then in this understanding, control should be made at the end of the execution of a management decision in order to establish the correspondence between the decision made and its executed version.